Pengaruh Marketing Mix dan Self Service Technology terhadap Loyalitas Nasabah Asuransi Salam Hijrah Amanah - Yulistiawati, Tia; Dimyati, Dadang; Halim, Asep Abdul (Ma'soem University, 2024)
This study aims to determine the effect of Marketing Mix and Self Service Technology on Customer Loyalty of Salam Hijrah Amanah Insurance at Bank Muamalat KCP Ujung Berung partially and simultaneously. The object of this research is Salam Hijrah Amanah Insurance Customer Loyalty at Bank Muamalat KCP Ujung Berung. The type of research is associative quantitative. The type of data in this study is primary data, and data collection techniques are in the form of observation, interviews, literature study, questionnaires. The population is 123 people, while the sample determination uses the slovin formula as many as 57 people.The results showed that there was a significant influence between the Marketing Mix and Customer Loyalty of Salam Hijrah Amanah Insurance, there was a significant effect between Self Service Technology on Customer Loyalty Salam Hijrah Amanah Insurance, and simultaneously there is a significant influence between Marketing Mix and Self Service Technology on Customer Loyalty of Salam Hijrah Amanah Insurance at Bank Muamalat KCP Ujung Berung.